A capabilities‐based perspective on target selection in acquisitions - Kaul, Aseem; Wu, Brian (Strategic Management Journal, 2016)
We develop a capabilities‐based theory of acquirer target selection, arguing that acquirers will pursue both low capability targets in existing contexts to deploy existing capabilities, and high capability targets in new contexts to acquire new capabilities. These arguments are formalized in an analytical model that jointly considers the benefits and costs of acquisition as a function of target capability level and context. The predictions from this model are tested in the C hinese brewing industry (1998–2007), with results showing that acquirers strongly prefer inferior targets in existing geographic markets, but are relatively more likely to choose superior targets in new markets, especially if they have strong acquisition capabilities. Our study provides insight into the factors driving target selection, and contributes to a capabilities‐based understanding of acquisitions . Copyright © 2015 John Wiley & Sons, Ltd.